Identification of the Clinical Candidate (R)‑(1-(4-Fluorophenyl)-6-((1-methyl‑1H‑pyrazol-4-yl)sulfonyl)-4,4a,5,6,7,8-hexahydro‑1H‑pyrazolo[3,4‑g]isoquinolin-4a-yl)(4-(trifluoromethyl)pyridin-2-yl)methanone (CORT125134): A Selective Glucocorticoid Receptor (GR) Antagonist - Hunt, Hazel J; Belanoff, Joseph K; Walters, Iain; Gourdet, Benoit; Thomas, Jennifer; Barton, Naomi; Unitt, John; Phillips, Timothy; Swift, Denise; Eaton, Emily (Journal of medicinal chemistry, 2017)
The nonselective glucocorticoid receptor (GR) antagonist mifepristone has been approved in the U.S. for the treatment of selected patients with Cushing’s syndrome. While this drug is highly effective, lack of selectivity for GR leads to unwanted side effects in some patients. Optimization of the previously described fused azadecalin series of selective GR antagonists led to the identification of CORT125134, which is currently being evaluated in a phase 2 clinical study in patients with Cushing’s syndrome.